Efektivitas Penerapan Media Pembelajaran Typing Master Terhadap Minat Belajar dan Keterampilan Mengetik 10 Jari Buta Siswa Kelas X Otomatisasi Tata Kelola Perkantoran di SMK Negeri 1 Enam Lingkung - Yuliandita Yuliandita; Elvi Rahmi (Universitas Negeri Padang, 2024)
This study aims to determine how much the Effectiveness of the Application of Typing Master Learning Media on Learning Interest and skills for Blind 10-finger Typing of Class X Office Management Automation Students at SMK Negeri 1 Enam Lingkung. This research type includes experiment research. The design for research used is Design by True Experimental with Pretest-Posttest Control Group Design type. The research population was all of SMK Negeri 1 Enam Lingkung class X students consisting of 51 students. The research sampling used the technique of total sampling, the sample amounted to 51 students of class X OTKP which is all the population in this study The research instrument used questionnaires and tests. Data analysis techniques using analysis, descriptively inductive, and hypothesis testing. The results of the research indicate that: 1) There is no distinction in student interest in learning from those who use Typing Master media and those who do not use Typing Master media in class X OTKP at SMK N 1 Enam Lingkung with sig results (2 tailed) 0.232 which means the significance value is bigger than 0.05. This can be caused by internal factors and internal factors. 2) There are differences in the blind 10-finger typing skills of students using media for Typing Master learning and those who do not use media of Typing Master learning in class X OTKP at SMK N 1 Enam Lingkung with sig test results (2-tailed) 0.012 <0.05. So , the application of Typing Master media is good to apply to learning to type 10 fingers blindly